Complex metodology of multi-criteria estimation of the effectiveness of scientific space projects - Воронин, А. Н.; Колос, Л. Н.; Подгородецкая, Л. В. (Problems of Informatization and Control, 2004)
A problem of the multi-criteria estimation of the effectiveness of scientific space projects is considered by expert estimates method. A notion of the nested scalar convolution is used. A method of analytical and qualitative estimates production is given. A technique of visualization is considered (“profile of a project”)